Individual Variability in Migration Timing Can Explain Long-Term, Population-Level Advances in a Songbird - Fraser, Kevin C.; Shave, Amanda; de Greef, Evelien; Siegrist, Joseph; Garroway, Colin J. (Frontiers in Ecology and Evolution, 2019)
Migratory animals may be particularly at-risk due to global climate change, as they must match their timing with asynchronous changes in suitable conditions across broad, spatiotemporal scales. It is unclear whether individual long-distance migratory songbirds can flexibly adjust their timing to varying inter-annual conditions. Longitudinal data for individuals sampled across migration are ideal for investigating phenotypic plasticity in migratory timing programs, but remain exceptionally rare. Using the largest, repeat-tracking data set available to date for a songbird (n=32, purple martin Progne subis), we investigated individual variability in migration timing across 7,000-14,000 kilometre migrations between North American breeding sites and South American overwintering sites. In contrast to previous studies of songbirds, we found broad, within-individual variability between years in the timing of spring departure (0-20d), spring crossing of the Gulf of Mexico (0-20d), and breeding site arrival (0-18d). Spring departure and arrival dates were consistent across years (depart r=0.61; arrive r=0.67), however the lower bounds of confidence intervals spanned 0.5 indicating that this finding should be cautiously interpreted until more data accumulates. Fall migration timing was more variable at the individual level (depart range= 0-19d; gulf crossing range range=1-15d; arrive range=0-24d). Fall arrival date was the least repeatable (r=0.002), perhaps due to timing of this leg being the least resource limited, as purple martins are not territorial in winter and join large communal roosts. High within-individual variability in the timing of this diurnal migrant may reflect the greater influence of environmental and social cues as compared to more solitary, nocturnally migrating songbirds. Further, large, within-individual variability in migration dates (0-24d) suggest that advances in spring arrival dates with climate change that have been reported for multiple songbird species (including purple martins) could potentially be explained by intra-individual flexibility in migration timing. However, whether phenotypic plasticity will be sufficient to keep up with the pace of climate change remains to be determined.